2012
DOI: 10.1121/1.4734555
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of alarm sounds

Abstract: Two approaches to the automated detection of alarm sounds are compared, one based on a change in overall sound level (RMS), the other a change in periodicity, as given by the power of the normalized autocorrelation function (PNA). Receiver operating characteristics in each case were obtained for different exemplars of four classes of alarm sounds (bells/chimes, buzzers/beepers, horns/whistles, and sirens) embedded in four noise backgrounds (cafeteria, park, traffic, and music). The results suggest that PNA com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Previous studies of automatic audible alarm recognition have been primarily in the settings of industrial and traffic alarms [7][8][9][10][11]. Approaches described in the literature have included sinusoidal modeling, machine learning, longest common sequence identification, and amplitude-based periodicity detection [12][13][14]. However, these methods' accuracy has generally been limited, and their performance under noisy conditions is poor.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of automatic audible alarm recognition have been primarily in the settings of industrial and traffic alarms [7][8][9][10][11]. Approaches described in the literature have included sinusoidal modeling, machine learning, longest common sequence identification, and amplitude-based periodicity detection [12][13][14]. However, these methods' accuracy has generally been limited, and their performance under noisy conditions is poor.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic alarm sound detection was previously investigated for the purposes of hearing impaired assistance and hearing support in noisy conditions [12] [14] . To our knowledge, research on the topic was first reported in [15] , where the detection of various real-world alarm sounds was addressed.…”
Section: Introductionmentioning
confidence: 99%
“…While the model-based approach is also followed in [12] , most of the posterior works adhere to the non-model-based approach. For instance, a simple signal processing based method was reported in [13] , where an autocorrelation function, used to exploit the long-term periodicity of alarms, is compared to a threshold. In [14] amplitude periodicity in a specific frequency bandwidth is detected using a decision tree based on zero-crossing rate of the autocorrelation of the signal envelope.…”
Section: Introductionmentioning
confidence: 99%
“…All tests were done at 0 dB signal-to-noise ratio (SNR), and both approaches were stated to perform poorly. A much simpler approach for automated detection of alarm sounds is described in [11]. Four classes of alarm sounds (bells/chimes, buzzers/beepers, horns/whistles, and sirens) are detected in four noise backgrounds (cafeteria, park, traffic, and music) based on the normalized autocorrelation function and the overall sound level.…”
Section: Introductionmentioning
confidence: 99%